Fire Safety and Concrete Performance in Malaysia: A Review of Incidents, Material Behavior, and Standard Testing Protocols - Ratihi, Noorhapsari; Sharma, Vikram Prasad; Otieno, Beatrice Achieng (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Fire incidents remain a critical and persistent challenge in Malaysia, posing significant threats to residential, educational, commercial, and environmental assets. This review synthesizes current knowledge on the Malaysian fire landscape, focusing on the behaviour of concrete structures under elevated temperatures, and examines standard testing protocols essential for assessing material resilience and structural safety. The analysis highlights an alarming frequency of annual fire events, which underscores the urgent need for a coordinated risk management strategy that engages both governmental agencies and private stakeholders. A central theme of the review is the thermo-mechanical performance of concrete, encompassing phenomena such as thermal expansion, spalling, residual compressive and tensile strength, and the effects of prolonged exposure to high temperatures. The study further evaluates the efficacy of material modifications, including fibre reinforcement, geopolymer formulations, and other innovative additives, in enhancing fire resistance and post-fire structural integrity. Additionally, the paper provides a detailed overview of critical international standards, including ASTM and ISO, for the mechanical and durability assessment of concrete after fire exposure, emphasizing their relevance and potential adaptation within the Malaysian context. The review concludes by highlighting the practical implications of these findings: the urgent need for integrated fire safety management, the adoption of advanced fire-resistant concrete technologies, and the enforcement of standardized testing and assessment protocols. Collectively, these strategies are essential to mitigate the devastating impact of fires on Malaysia’s built environment, safeguard human life, and ensure long-term structural resilience.